2015
DOI: 10.1515/zpch-2015-0610
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Solutions Probed by Resonant Inelastic X-ray Scattering

Abstract: X-ray spectroscopy is a powerful tool to study the local charge distribution of chemical systems. Together with the liquid jet it becomes possible to probe chemical systems in their natural environment, the liquid phase. In this work, we present X-ray absorption (XA), X-ray emission (XE) and resonant inelastic X-ray scattering (RIXS) data of pure water and various salt solutions and show the possibilities these methods offer to elucidate the nature of ion-water interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…X-ray spectroscopy allows measuring directly the electronic properties of a system and provides direct information about the local electronic structure around a specific element in a bulk chemical environment. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Previous soft X-ray absorption studies on aqueous solutions reported strong distortions of the pre-, main-and post edge of the X-ray absorption spectra on the oxygen K-edge in the vicinity of the ions. 7,30,31,33 These changes have been assigned to weakening and strengthening of the hydrogen bonds in the solvation shell around the cations.…”
Section: Tocmentioning
confidence: 99%
See 3 more Smart Citations
“…X-ray spectroscopy allows measuring directly the electronic properties of a system and provides direct information about the local electronic structure around a specific element in a bulk chemical environment. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Previous soft X-ray absorption studies on aqueous solutions reported strong distortions of the pre-, main-and post edge of the X-ray absorption spectra on the oxygen K-edge in the vicinity of the ions. 7,30,31,33 These changes have been assigned to weakening and strengthening of the hydrogen bonds in the solvation shell around the cations.…”
Section: Tocmentioning
confidence: 99%
“…27,35,36 Recently, several soft XES experiments have reported that the electronic properties of water is altered by the presence of salt ions only at high salt concentrations. 28,[37][38][39][40] However, the dominating change that is observed is an intensity decrease of the lower energy part of the split lone pair orbital peak in dependence of the concentration and the type of salt ions, which consisted mainly of Clas anion and various cations (NH 4 + , Li + , K + , Na + , Mg 2+ & Ca 2+ ). These changes were assigned to the distortion of the hydrogen bond network.…”
Section: Tocmentioning
confidence: 99%
See 2 more Smart Citations
“…Life-relevant motions, however, can be as slow as seconds or even up to minutes' or hours' time scales. The origin of these time scale differences is based on the complexity of the coordination space of a proceeding reaction [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%